Alumbrado público del polideportivo Ospina Pérez uso de tecnología led (2021)
The purpose of this degree work is to design the public lighting system for the sports center Ospina Pérez in the city of Cúcuta Norte de Santander, applying the latest trends in public lighting for sports fields that are being developed in the country, such as LED-type technologies, which have been used massively in recent years, seeking the reduced environmental impact negative through significant improvements in energy efficiency. The design focuses on the projection of the infrastructure, calculations and design of the lighting system for the sports center, using Led technology and applying the regulations of the RETIE and RETILAP.